Evaluation of the competition between alfalfa and sainfoin sown in mixture - Delgado I.; Muñoz F.; Andueza D. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Alfalfa and sainfoin are pluriannual forage legumes that are well adapted to the agronomic conditions of NE Spain. However the persistence of sainfoin decreased when sown with alfalfa in mixture. It could be attributed to the fact that the cutting frequency was more suitable for alfalfa. In order to evaluate the persistence of sainfoin in mixture, the evolution of the annual forage yield in these species was compared, when sown in pure stands or using two types of mixtures, on alternate rows or mixed on the same row. Two harvesting rates were established, one that was most suited to alfalfa and the other to sainfoin. The study was conducted in rainfed conditions in Badules (Teruel) and under irrigation in Zaragoza during 2011-2013. The results confirm the lower yields and persistence of sainfoin when mixed with alfalfa under irrigation, which could be attributed to the allelopathic effects of alfalfa on sainfoin. There is no evidence of allelopathic phenomena arising in rainfed conditions in the two sowing modes employed. Cutting frequency had no influence on the occurrence of allelopathic phenomena.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)